Bioavailability Assessment of the Novel Gsh-Functionalized Feb Nanoparticles Via Oxidative Stress and Trace Element Metabolism in Vitro: Promising Tools for Biomedical Applications - Aydemir, Duygu; Çağıran, Özge Balcı; Aribuga, Dilara; Hashemkhani, Mahshid; Acar, Havva Yagci; Çağıran, Özge Balcı; Ulusu, Nuriye Nuray (Springer, 2024)
Iron-based magnetic nanoparticles (NPs) have attracted significant attention in biomedical research, particularly for applications such as cancer detection and therapy, targeted drug delivery, magnetic resonance imaging (MRI), and hyperthermia. This study focuses on the synthesis and glutathione (GSH) functionalization of iron boride (FeB) nanoparticles (NPs) for prospective biomedical use. The GSH-functionalized FeB NPs (FeB@GSH) demonstrated ferromagnetic behavior, with a saturation magnetization (Ms) of 45.8 emu/g and low coercivity (Hc = 1000 Oe), indicating desirable magnetic properties for biomedical applications. Transmission electron microscopy (TEM) analysis of the FeB@GSH revealed well-dispersed nanoparticles with diameters smaller than 30 nm. Comprehensive nanotoxicity and biocompatibility assessments were performed using various healthy and cancer cell lines, including 293 T, HeLa, 3T3, MCF7, HCT116, and CFPAC-1. Cytotoxicity assays were conducted on FeB@GSH-treated cells over a dose range of 0-300 mu g/mL during 24-h incubations. Results indicated no significant differences in cell viability between treated and untreated control groups, confirming the biocompatibility of FeB@GSH. Further nanotoxicity evaluations were carried out on 3T3, 293 T, and CFPAC-1 cell lines, focusing on oxidative stress markers and cellular metabolism by measuring antioxidant enzyme activity. Additionally, ion release and mineral metabolism were assessed using inductively coupled plasma mass spectrometry (ICP-MS), revealing no notable variations between the treated and control groups. These findings suggest that FeB@GSH NPs exhibit excellent biocompatibility, making them promising candidates for diverse biomedical applications, including medical imaging, drug delivery systems, and therapeutic interventions.
Keywords: Oxidative stress; Biocompatibility; FeB; Nanobiomedicine; Ferromagnetic NPs; GSH functionalization; Trace elements